2017
DOI: 10.5603/arm.2017.0014
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Trends in Inpatient Admissions of Pulmonary Hypertension in the United States from 2000 to 2013

Abstract: Introduction: Pulmonary Hypertension (PH) is a disorder of the pulmonary vasculature with high mortality and bears a large economic burden on the healthcare system. We conducted a review of the largest inpatient database in the United States and analyzed the trends in hospitalizations due to PH from the turn of the century (2000) to 2013 to evaluate the rate of hospitalizations and determine the cost and mortality associated with PH. Conclusion:The number of inpatient discharges related to PH has increased ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…In patients with pulmonary hypertension, recent studies have reported a 13% increase in hospital LOS (11.8 days longer), initial diagnosis at an older age (> 65 years), a small percentage patients with private insurance, doubled hospital charges, and a 23% decrease in mortality [ 8 ]. Mortality has decreased due to advancements in treatment and the new pharmacotherapies that are now available.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with pulmonary hypertension, recent studies have reported a 13% increase in hospital LOS (11.8 days longer), initial diagnosis at an older age (> 65 years), a small percentage patients with private insurance, doubled hospital charges, and a 23% decrease in mortality [ 8 ]. Mortality has decreased due to advancements in treatment and the new pharmacotherapies that are now available.…”
Section: Discussionmentioning
confidence: 99%
“…2 Using the National Inpatient Sample Database to identify PH or cor pulmonale as the primary discharge diagnosis from 2000 to 2013, the authors found increased admissions for PH in terms of absolute numbers, mean length of stay, and hospital charges. 3,4 In fact, the overall cost of hospital visits of a patient increased by 209.5% from $301,324,218 in 2000 to $932,554,725 in 2013. 4 These inpatient costs associated with PH contribute significantly to the total health care burden.…”
Section: Hospitalization and Phmentioning
confidence: 99%
“…3,4 In fact, the overall cost of hospital visits of a patient increased by 209.5% from $301,324,218 in 2000 to $932,554,725 in 2013. 4 These inpatient costs associated with PH contribute significantly to the total health care burden. With advances in PH treatment options and increased use of combination therapy, medication costs are rising.…”
Section: Hospitalization and Phmentioning
confidence: 99%
“…PH is under-diagnosed and diagnosis is often made late with a median survival of only 2.8 years [ 12 ]. A diagnosis of PH also increases the cost of inpatient admissions; a study found that the aggregate cost of hospital visits of a patient in the United States with the principal diagnosis of PH increased 209.5% from $301,324,218 in 2000 to $932, 554, 725 in 2013 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%